Theoretical analysis of development of psychological representation during Antiquity - Dmitry Larin (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article presents a theoretical analysis of the development of psychological ideas in the period of Antiquity, presented the concept of animism and Hylozoism. The author offers a new perspective on the development of early ideas about the subject of psychology in the works of Aristotle, Socrates, Plato, and other representatives of ancient psychology. In conclusion, there is the role of philosophy in the ancient period, which had a prevailing influence in the development of the subject of psychology.